2006
DOI: 10.1128/jcm.44.3.1059-1064.2006
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Ciprofloxacin Resistance from Point Mutations in gyrA and parC Confined to Global Hospital-Adapted Clonal Lineage CC17 of Enterococcus faecium

Abstract: To substantiate a common genetic background of ciprofloxacin-resistant Enterococcus faecium, 32 ciprofloxacin-resistant (Cip r ) and 31 ciprofloxacin-susceptible (Cip s ) isolates from outbreaks, clinical infections, surveillances, and animals from 10 different countries were genotyped by multilocus sequence typing. Additionally, susceptibilities to ampicillin and vancomycin and the presence of esp were determined and the quinolone resistance-determining regions of parC, gyrA, parB, and gyrE were sequenced. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 61 publications
4
71
1
3
Order By: Relevance
“…97% of those isolates showed ciprofloxacin resistance according to antibiotic susceptibility testing. Ser80→Arg mutation of parC and Ser83→Arg mutation of gyrA were most commonly found in 17 of 37 isolates (45.9%), and these mutations are known as most frequently observed mutations in QRDR [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…97% of those isolates showed ciprofloxacin resistance according to antibiotic susceptibility testing. Ser80→Arg mutation of parC and Ser83→Arg mutation of gyrA were most commonly found in 17 of 37 isolates (45.9%), and these mutations are known as most frequently observed mutations in QRDR [13].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that genetically similar VREs are prevalent in this study. The genetic background of quinolone resistant E. faecium and its relation with CC17 were proved in Holland in 2005 [13]. MLST revealed that most of isolates belonged to CC17 and consequently investigation on CC17 as possible genetic aberrations causing quinolone resistance was made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and the necessity of specific mutations in one or both A subunit genes to confer what is specified as high-level ciprofloxacin resistance (Onodera et al, 2002;Oyamada et al, 2006a;Oyamada et al, 2006b). Molecular studies with high-level ciprofloxacin-resistant clinical isolates revealed mutations in both A subunits associated with different levels of ciprofloxacin resistance, whereas mutations in gyrB and parE alleles were only infrequently found Leavis et al, 2006;Valdezate et al, 2009;Werner et al, 2010a).…”
Section: Fluoroquinolone Resistancementioning
confidence: 99%
“…Classification into susceptible/intermediate/resistant (S-I-R) differs between European Committee on Antimicrobial Susceptibility Testing (EUCAST) and Clinical Laboratory Standard Institutes (CLSI) (CLSI, 2011); EUCAST defines MICs for vancomycin with S ≤ 4 mg/L and R > 4 mg/L (no intermediate range) and CLSI defines S ≤ 4 mg/L, I = 8-16 mg/L, and R ≥ 32 mg/L. We used the EUCAST clinical breakpoints when available; for other antibiotics, we applied breakpoints derived from CLSI, DIN, and based on other criteria, e.g., for high-level ciprofloxacin resistance defined as an MIC > 16 mg/L ( Leavis et al, 2006 andWerner et al, 2010). Strains were classified as resistant with MICs (in milligrams per liter) as follows: penicillin/ampicillin > 8, teicoplanin > 2, erythromycin > 4, linezolid > 4, tetracycline > 4, rifampicin > 0.5, chloramphenicol > 16, tigecycline > 0.5, daptomycin > 4, gentamicin (high-level) > 128, streptomycin (high-level) > 512, quinupristin/dalfopristin > 4.…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 99%